Relationship between clinical and electromyographic findings and exposure to solvents, in shoe and leather workers. Issue 2 (May 1978) - Buiatti, E; Cecchini, S; Ronchi, O; Dolara, P; Bulgarelli, G
Abstract : A very high prevalence of polyneuropathy was observed in shoe and leather workers from the area of Florence. In addition, normal workers showed abnormally low maximal nerve motor conduction velocity. A linear decrease of motor conduction velocity was observed as a function of age and of the length of exposure to solvents. The worker population showed a steeper decrease with age than controls. A higher prevalence of polyneuropathy was observed when the amount of glue used by each worker per day was higher, and when the air volume of the plant was smaller. The subjective symptoms most frequently associated with polyneuropathy were muscle spasms, leg weakness and pain, and arm paresthesiae. Cases of polyneuropathy were more frequent in the workers exposed to solvents and in the older age group. A solvent aetiology of the disease is suggested, and glue substitution and proper hygienic conditions are recommended.